THE INFLUENCE OF RECRUITMENT PROCESS ON PERFORMANCE OF NEW EMPLOYEES AT 5 STAR HOTEL JAKARTA - Fathin, Amirah; Ningrum, Lestari; Abas, Ahmad Junaedi (Universitas Persada Indonesia YAI, 2019)
ABSTRACTThis study examines the effects of the recruitment process to performance at 5 Star Hotel Jakarta.Recruitment process is an independent variable, performance is dependent variable. Explanatory research withdescriptive and correlation method is new employees.The number of sample is 101 respondents. The purposive sampling technique is applied with criteria at 5Star Hotel Jakarta. Data are collected with questionnaires and processed with data analysis.These results indicate that the reliability test was very high (0.880) and based on 22 instruments statementonly 1 was invalid. It showed that 101 new employees as respondents consistently answered because theyunderstood and experienced. Each variable has an average value of 4.11 for the recruitment process that isimportant for new employees and 4.16 for performance that is well. The recruitment process has a lowcorrelation with performance is 0.329. The recruitment process also has a little effect on performance is 10.8%.Based on these results, This 5 Star Hotel should improve the recruitment procedure, increase a conducive,and comfortable working atmosphere.